Mathematical modeling using coordination mechanisms for multi-agent systems in service oriented architecture - Muhamad Ibrahim, Najhan (IIUM, 2019)
A heterogeneous communications mechanism is essential between different types of SOA applications to ensure the communications will be well maintained. The need for heterogeneous communications within SOA has attracted different research efforts as reported in various literature. This research interest is specifically focused on interoperability of heterogeneous communications in multiple types of SOA applications. The study of the coordination problem is an important issue in the multi-agent system. In the current software development industry, most software products are produced with the expectation that the application will provide intelligent coordination with the minimum level of interruption. This case is not always acceptable especially for the critical system especially those that deal with complex communications that involved multiple types of participants where the partner application needs to know about the basic guide and specification of each other. The proposed solution is dealing with one of these issues as it evaluates the coordination between the partner applications where the accuracy of responding is involved. For this reason, we modeled the proposed system mathematically using Coordination mechanisms to validate and verify the system for heterogeneous communications in SOA system.